The Failure of Hooker’s Argument for Rule Consequentialism - Levy, Sanford (2014)
Brad Hooker argues for rule consequentialism using narrow reflective equilibrium resources along with a handful of wider resources. One of his important claims in defense of rule consequentialism is that it begins from a familiar and attractive idea about morality. I argue that his defense of rule consequentialism fails and more particularly, that rather than beginning from a familiar and attractive idea, it begins from an idea that is quite unattractive. I show this by applying the method rule consequentialists use to derive moral advice for the real world to non-moral cases where its unattractiveness is clear. I then argue that the basic idea behind rule consequentialism is attractive if considered as an account of moral reform, in so far as the account of moral reform can be divorced from one’s account of right and wrong, something that occurs in theories like that of Stephen Toulmin.
Keywords: Moral Theory; Utilitarianism; Rule Utilitarianism; rule consequentialism; Hooker; Consequentialism